2003
DOI: 10.1086/378619
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Haptic Information Processing: The “Need for Touch” Scale

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 138.38.0.53 on Sun, This research details the development of the "Need for Touch" (NFT) scale designed to measure individual differences in prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
624
4
15

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(687 citation statements)
references
References 43 publications
21
624
4
15
Order By: Relevance
“…This result is consistent with findings of previous studies related to fashion innovativeness: Consumers with higher fashion innovativeness tend to engage more often in experiential shopping that is motivated by a desire for pleasure rather than practical purposes (e.g., Cho & Workman, 2011;Peck & Childers, 2003). Thus, those individuals with higher levels of fashion/brand leadership would find mobile devices more enjoyable compared to those with lower levels of fashion/brand leadership.…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with findings of previous studies related to fashion innovativeness: Consumers with higher fashion innovativeness tend to engage more often in experiential shopping that is motivated by a desire for pleasure rather than practical purposes (e.g., Cho & Workman, 2011;Peck & Childers, 2003). Thus, those individuals with higher levels of fashion/brand leadership would find mobile devices more enjoyable compared to those with lower levels of fashion/brand leadership.…”
Section: Discussionsupporting
confidence: 90%
“…In a study looking at touch by others, Argo, Dahl, and Morales (2006) showed that consumers react negatively if they believe products have already been touched by others. Childers (2003a, 2003b) demonstrated the importance of individual-level differences in haptic orientation or preference for productbased haptic information.Thus, the effect of the perceived haptic properties of products would appear to have significant implications for consumer behavior. Research in this emerging area has concentrated primarily on touch versus no-touch conditions, rather than manipulating the quality of the touch-related input (McDaniel and Baker 1977).…”
mentioning
confidence: 99%
“…Customers can touch the product in offline stores, but if they cannot touch the product when making purchase online. (Peck & Childers, 2003) [18] found that product's intrinsic cues such as tactility, color or smell (cues which, if changed would produce a resultant change in the physical product itself) are more important in a product's perceived quality than its extrinsic cues.…”
Section: Virtual Touchmentioning
confidence: 99%